Antioxidant and Anti-Inflammatory Activity of a New Formulation of Slow-Release Amino Acids in Human Intestinal Caco-2 Cells - Carlotta Bollati; Martina Tosi; Lorenza d’Adduzio; Melissa Fanzaga; Alberto Burlina; Gianvincenzo Zuccotti; Carmen Lammi; Elvira Verduci (Antioxidants)
Phenylalanine (Phe)-free protein substitutes (PSs) are used to provide an adequate intake of amino acids (AAs), except Phe, allowing control of blood Phe levels in patients with Phenylketonuria (PKU). Although indicated as a standard dietary treatment for these patients, free AAs mixtures are not absorbed as natural proteins, thus creating an oxidized and inflamed state in the intestine. Nowadays, PSs on the market also include slow-release amino acids (SR-AAs) formulas. The present work aims to investigate the effects of an SR-AAs formula on both oxidative and inflammatory status in human intestinal Caco-2 cells, comparing its mechanism of action with that of a mixture of free AAs. In more detail, oxidative stress and inflammation were induced at the cellular level using H2O2 and lipopolysaccharides (LPSs), respectively, and both free AAs and SR-AAs PSs were tested to evaluate if they were able to restore a more balanced condition. According to our findings, free AAs aggravate the intestinal oxidative and inflammatory status caused by H2O2 and LPS in human intestinal Caco-2 cells, which SR-AAs significantly improve. In conclusion, our results offer preclinical novelty on these products’ mechanisms of action, thus improving the dietary management of patients with PKU.